Meiosis - Bernstein, Carol; Bernstein, Harris (IntechOpen, 2013)
Meiosis is the key process underlying sexual reproduction in eukaryotes, occurring in single-celled eukaryotes and in most multicellular eukaryotes including animals and most plants. Thus meiosis is of considerable interest, both at the scientific level and at the level of natural human curiosity about sexual reproduction. Improved understanding of important aspects of meiosis has emerged in recent years and major questions are starting to be answered, such as: How does meiosis occur at the molecular level, How did meiosis and sex arise during evolution, What is the major adaptive function of meiosis and sex. In addition, changing perspectives on meiosis and sex have led to the question: How should meiosis be taught. This book proposes answers to these questions, with extensive supporting references to the current literature.